MICROBIOLOGICAL AND PHYSICOCHEMICAL EVALUATION OF RAW WATER SAMPLES PROCESSED IN A SIMPLIFIED WATER TREATMENT SYSTEM (REMUNOM, 2025)
Water plays a vital role in the health and survival of living organisms. However, it can also be a means of dissemination of pathogenic microorganisms, such as total coliforms and Escherichia coli, which are indicators of contamination. The aim of this study was to analyze the physicochemical and microbiological parameters of water submitted to treatment, in order to verify its potability and evaluate the effectiveness of the treatment process used. Raw water samples were collected from the Amazon River and Lake Serpa, and laboratory analyses were performed to determine the parameters of pH, turbidity, temperature and free residual chlorine concentration. The results were compared with established guidelines and regulations. The present study evaluated the efficiency of two coagulants (MTH® and MT®) in the treatment of raw water from the Amazon River and Lake Serpa, based on physicochemical (pH, turbidity, temperature and free residual chlorine) and microbiological (total and thermotolerant coliforms) parameters. The results demonstrated that, after treatment, the pH and turbidity values ​​remained within the limits established by current environmental legislation. Microbiological analyses indicated the absence of coliforms in all treated water samples, confirming the effectiveness of the process in removing pathogenic microorganisms. Thus, it is concluded that the simplified water treatment system evaluated is efficient and safe for human consumption, as long as continuous monitoring of water quality is maintained. Based on the results obtained in this study, it can be concluded that the water treatment process using MTH® and MT® coagulants was effective in reducing microbiological and physical-chemical contamination. Maintaining compliance with established quality standards is crucial to ensure the safety of the treated water supply. Regular monitoring of the quality of treated water is essential to protect public health and prevent the transmission of water-related diseases.